The 15-item version of the Boston Naming Test in Italian: normative data for adults. Issue 1 (2nd January 2023) - Vestito, Lucilla; Mori, Laura; Trompetto, Carlo; Tomatis, Marina; Alessandria, Giulia; De Carli, Fabrizio; Cocito, Leonardo; Bandini, Fabio
ABSTRACT: Background: The Boston Naming Test (BNT) is a neuropsychological tool that is widely utilized in clinical practice to detect naming difficulties (i.e., anomia) in patients with language disorders and to evaluate the semantic memory integrity in patients with cognitive impairment (i.e., Alzheimer's Disease). The complete version of the test includes 60 items, but several abbreviated forms have been developed in order to shorten the time of administration. These shortened versions have also been translated and adapted in countries where English is not the primary language. It is still necessary, however, to collect normative data from other languages, including Italian. Aims: The purpose of the current study was to introduce the first Italian version of the 15-item BNT for adults that is comparable to the original English version and to provide normative data based on 275 healthy Italian-speaking adults stratified by age, sex and education. Finally, we assessed the qualitative differences in erroneous answers in order to detect normal incorrect patterns of response. Methods and Procedures: The 15-item Form 4 proposed by Mack and collaborators, which is included in the latest version of the BNT (2001), was administered to 130 males and 145 females, aged between 18 and 85 years, with a formal education ranging from 5 to 32 years. The 15 items of the original English BNT were double translated, achieving an appropriate cross-linguistic and cross-cultural comparison. The statistical analysis was performed applying a generalized linear regression model with inverse Gaussian distribution of the response variables. Pearson's correlation coefficient was utilized to investigate the relationship between the pattern of responses and the demographic variables. Results: We provided data for educated Italian adults from multiple age groups stratified by gender and educational background. In addition, our results demonstrate that demographic variables, mostly at the schooling level, play an important role in naming performance, with higher levels of education being strongly associated with better performance Conclusions: We suggest that this 15-item BNT is a suitable tool for the assessment of naming ability in the adult Italian population.